2010
DOI: 10.4028/www.scientific.net/amr.163-167.3138
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Method for Predicting Chloride Concentration Distributing around Reinforcement in Concrete

Abstract: The reinforcement in concrete alters the pathway for chloride transporting and in turn causes the chloride concentration to accumulate faster near the reinforcement closest to the exposed surface. A mass conservation matrix equation under the non-stable diffusion based on the Fick’s second law was derived. Hereby, a numerical simulation method for predicting chloride concentration in concrete was established utilizing the compiled module based on FEA. The validity of the method was verified by the comparison w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Oh and Jang [10] found that the corrosion initiation time dropped by 30~40% after the addition of rebar, an evidence to the chloride accumulation at the apex of rebar. Kranc [11] and Wang [12] argued that the effect of rebar is nonnegligible in the calculation of chloride ion distribution in RC concrete. Comparing the results of a 1D model and a 2D model, Yu [6][7]13] concluded that the rebar with a big size, a thin cover and a flat front face can accelerate chloride accumualtion and reduce the initiation time.…”
Section: Introductionmentioning
confidence: 99%
“…Oh and Jang [10] found that the corrosion initiation time dropped by 30~40% after the addition of rebar, an evidence to the chloride accumulation at the apex of rebar. Kranc [11] and Wang [12] argued that the effect of rebar is nonnegligible in the calculation of chloride ion distribution in RC concrete. Comparing the results of a 1D model and a 2D model, Yu [6][7]13] concluded that the rebar with a big size, a thin cover and a flat front face can accelerate chloride accumualtion and reduce the initiation time.…”
Section: Introductionmentioning
confidence: 99%